Seroprevalence of Hepatitis C Infection among Laboratory Health Care Workers in Isfahan, Iran - Shoaei, Parisa (Medknow Publications & Media Pvt Ltd, 2012)
OBJECTIVES: Clinical laboratory health care workers can become infected through their occupation with blood-borne pathogens by percutanous injuries and mucocutaneous blood contacts such as cuts, needle sticks, splashes to mucous membranes or other body injuries. The purpose of this study was to determine the seroprevalence of, Hepatitis C virus (HCV), and some of the risk factors in medical laboratory health care workers. METHODS: Through a descriptive cross sectional study, 203 participants employed in the clinical laboratories of the city of Isfahan, composed of medical laboratory technologists, technicians and cleaning staff were studied. Participant data were obtained through a self-reporting questionnaire and the level of anti-HCV antibody was measured by enzyme linked immunosorbent assay (ELISA). Chi-square test was used to determine risk factors associated with infection. RESULTS: The mean age of the individuals (n = 203) was 35.8 ± 9.54 years. There were 115 women (56.7%) and 88 men (43.3%). All of the subjects were negative for HCV Ab. CONCLUSIONS: Hepatitis C infection is infrequent in laboratory health care workers in Isfahan province.